Miras as a distance indicator in the CSST, JWST, and Gaia era - Sun, Yan; Zhang, Jingdong; Zhang, Bo; Xu, Shuangjing; Mai, Xiaofeng; Ding, Hao; Chen, Wen; Wen, Shiming (Frontiers in Astronomy and Space Sciences, 2023)
Mira variables are important distance indicators owing to clear Period-Luminosity Relation at infrared wavelengths. We have compiled a sample of 343 Galactic Miras selected from the American Association of Variable Star Observers (AAVSO) database and Gaia Data Release 3 (DR3). We used V-band observations from AAVSO to generate template light curves and derived mean magnitudes in near-infrared JHK band from Two Micron All-Sky Survey (2MASS). Based on Gaia-2MASS diagram and Gaia-LPV2 catalogue, we classified 299 O-rich and 44 C-rich Miras.We fitted the Galactic Period-Luminosity Relations for O-rich Miras in near-infrared JHK band and estimated slopes (-2.74 ± 0.32, -3.14 ± 0.30, -3.50 ± 0.25) and zero-points (-5.58 ± 0.06 mag, -6.40 ± 0.06 mag, -6.84 ± 0.05 mag) defined at logP(days) = 2.30, separately. Although the uncertainties of our derived Galactic PLRs for Miras are still larger than those of other galaxies, the multi-band sky survey by the China Space Survey Telescope (CSST) could help to build more reliable and accurate PLRs for Miras, especially in near-infrared y band (927-1080 nm).